Isolation and biochemical diagnosis of cell lines of groundnut (Arachis hypogaea L) selected on glyphosate - Jain, M; Bhatnagar, R.K; Sarin, N.B (Pesticide Science, 1999)
Three cell lines of groundnut (Arachis hypogaea L), an important oilseed legume, were selected on glyphosate using in-vitro culture techniques. The cell lines isolated through single as well as stepwise selection procedures showed c 20-fold increase in glyphosate tolerance as compared to the unselected control cell line. Studies on the biochemical mechanism of glyphosate tolerance in these cell lines showed a significant increase in the total extractable activity of the target enzyme, 5-enolpyruvyl shikimate-3-phosphate (EPSP) synthase (EC 2.5.1.19), which was further confirmed with immunological data. The over-expressed EPSP synthase activity was, however, subject to inhibition by glyphosate in vitro. Two other key regulated enzymes of the shikimic acid pathway, 3-deoxy-D-arabino heptulosonate 7-phosphate (DAHP) synthase (EC 4.1.2.15) and chorismate mutase (CM) (EC 5.4.99.5) did not show any change in specific activity in the selected cell lines. The enhanced activity of EPSP synthase in the tolerant cell lines was found to be stably inherited in the absence of selection pressure.